Effectiveness of Concrete Tiles Made from Medical Waste Incineration Residue Admixture - Anggreini Beta Citra Dewi; Fathoni Firmansyah; Siti Rachmawati; Prabang Setyono; Jilan Ashila; Iwan Suryadi (Poltekkes Kemenkes Surabaya, 2025)
Incineration is a widely used method for processing solid waste, involving a high-temperature combustion process that generates various residues, including bottom ash. Bottom ash is one of the residues that is produced. Bottom ash contains heavy metals that are harmful to the environment, one of which is nickel (Ni). This study aims to evaluate the concentration of Ni in medical waste incineration ash and concrete roof tiles produced using ash mixtures, while also assessing the impact of ash addition on the flexural strength and impermeability of these tiles. The Toxicity Characteristic Leaching Procedure (TCLP), following the Indonesian National Standard (SNI 7184.3:2011), was employed for heavy metal analysis. The test results on medical waste incineration ash showed that the Ni metal content was 0.33 mg/L, while the test results on concrete roof tiles varied 10%, 20%, and 30%, respectively, at 0.18 mg/L, 0.21 mg/L, and 0.39 mg/L. These values fall below the permissible threshold specified in Indonesian Government Regulation PP 22 of 2021. When testing the flexural strength of roof tiles with variations of 10%, 20%, and 30%, the results were 654 N, 1018 N, and 754 N. Based on these results, the flexural strength of concrete roof tiles is below the flexural strength standard in SNI 0096:2007. Water impermeability tests, however, showed no signs of water penetration across all variations, meeting the SNI 0096:2007 standard for water resistance.